Development of an automatic monitoring system for ground settlement induced by shield tunnelling. Issue 1 (January 2020) - Wan, Shifu; Huang, Qiming; Zhao, Hailin; Qi, Xingxin; Liu, Yi; Qiu, Wenge
Abstract: During the construction of the modern subway, it is often the case that subway tunnel construction is close to existing buildings, causing the deformation of existing buildings. In order to minimize the impact of new line construction, real-time monitoring and feedback warning of building deformations are required. This paper is based on the current mature automated monitoring data acquisition system. A comprehensive monitoring management system is developed, which includes engineering information management, monitoring equipment management, monitoring data reception, monitoring data analysis and processing, early warning information release as well as monitoring report automatic output. The developed automatic monitoring system was applied to the monitoring of the construction of Chengdu Metro Line 5, completed the automatic monitoring and real-time data processing and early warning of the underpass process. The operation safety of the existing lines was guaranteed. In the future, this system will also be extended to other tunnel monitoring, gradually forming a comprehensive tunnel construction monitoring and management system.